Facial identification for computerized people access control systems using neural networks - Borja, Mario (2007)
In this project, image recognition will be applied through neural networks for facial identification, which will be used for the implementation of systems computerized access control of people, where the identification of faces of people, which will be captured in real time with cameras located at points Strategic access in restricted areas. Based on this experience, the solution to the facial identification problem, based on the facial recognition problem patterns. It is worth mentioning that this research, in addition to solving the problem of Facial identification also considers the creation of software in the form of libraries or modules that can be used for future applications in commonly used language like C++ in any of its presentations and with this it is hoped to create a base for the development of commercial software And finally we also intend to analyze the general problem of pattern recognition, since a recognition could be made to many products, using the same principle, that we use in this project.